Handshake, No. 15 (October 2014) - World Bank Group (Washington, DC, 2015)
This issue includes the following headings: finding the right broadband public-private partnership (PPP): whats key for emerging economies?; reform has its rewards: telecom takes off in Myanmar; e-gov excellence: models from Colombia, Ghana, India, and Portugal; know what you know: creating a government technology strategy; and closing the gap: Facebook and intel connect the unconnected.